Analysis of Logistics Distribution Channels in Goods Supply to Increase Sales Volume at Logistics Company - Rahmat Hidayat; Euis Saribanon; Agus Suhendra; Suprihadi, Suprihadi; Alfais Amin Darmawan (Dinasti International Journal of Economics, Finance & Accounting, 2024)
A logistics company is a distribution channel company that provides goods delivery transportation through product packages. The problem raised in this thesis is the analysis of logistics distribution channels in the supply of goods to increase sales volume. This research aims to determine and analyze the distribution channels and sales levels of a logistics company and to determine the influence of distribution channels on the sales volume levels of a logistics company To solve the problem the author used two research methods, namely the data collection method and the data analysis method. The data collection method was carried out using questionnaires and the data analysis method used simple correlation and regression. From the results of the analysis, the author concludes that 78.7% of customers rate the distribution channels provided by logistics companies highly, and 78.3% of customers rate the level of sales volume provided by logistics companies correlation coefficient of 0.737 means that the influence of the distribution channel level on the level of sales volume is very high. The determining coefficient of 54.3% is determined by the distribution channel and the remaining 45.7% is influenced by other factors, the results of the t-test calculation, where ????count = 5.763 while ????????????????????e=1.701. So, ????count > ????????????????le or 5,763 > 1.701. This means that there is a positive and significant influence between distribution channels on the sales volume level of the logistics company. Keyword: Logistics, Transportation, Cargo, Distribution Channels, Sales.